The Effective and Appropriate Teaching Methods of Reading, Writing, and Arithmetic (Calistung) for Grade 1–3 Students in Madrasah Ibtidaiyah - Umi Salamah; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
This study examines the teaching of reading, writing, and arithmetic (Calistung) in the early grades of Madrasah Ibtidaiyah (MI) as a fundamental foundation for literacy and numeracy mastery. The objectives of this research are to explain the basic principles of effective Calistung instruction, to describe appropriate teaching methods, and to analyze the roles of teachers and parents in supporting successful learning. The theoretical framework highlights several principles, namely gradual and continuous learning, a concrete-to-abstract approach, student-centered strategies, and the integration of Islamic values. Relevant teaching methods include the phonetic method, syllabic method, play-based learning, contextual learning, and multisensory approaches. The findings emphasize that students in early MI grades are still in the concrete operational stage; thus, the use of tangible media and enjoyable activities proves more effective in enhancing comprehension. Furthermore, parental involvement in providing consistent learning practices at home serves as a crucial factor that reinforces students’ achievements at school. Therefore, effective Calistung learning in MI requires teachers’ creativity in combining various methods and strong collaboration between school and family to support the development of children’s literacy and numeracy skills.